The development of socialism, social democracy and communism : historical, political and socioeconomic perspectives - Sabry, Mohamed Ismail (Emerald Publishing Limited, 2017)
This book examines how socioeconomic and institutional factors shaped the development of Socialism and its two contending variants of Social Democracy and Communism, investigating why each of these factions enjoyed varying levels of popularity in different societies between 1840 and 1945.
Keywords: Socialism.; Communism.; Democracy.; Economics -- Sociological aspects.; Institutional economics.; elektronické knihy; electronic books